Their morals and ours : marxist versus liberal views on morality - Trotski, Leon; Dewey, John; Novack, George (New York : Merit Publishers, 1966)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: marxisme; liberalisme; morele waarden